Characterization of METTL7B to Evaluate TME and Predict Prognosis by Integrative Analysis of Multi-Omics Data in Glioma - Chen, Xiaochuan; Li, Chao; Li, Ying; Wu, Shihong; Liu, Wei; Lin, Ting; Li, Miaomiao; Weng, Youliang; Lin, Wanzun; Qiu, Sufang (Frontiers in Molecular Biosciences, 2021)
Glioma is the most common and aggressive type of primary brain malignant tumor with limited treatment approaches. Methyltransferase like proteins 7B(METTL7B) is associated with pathogenesis of several diseases but rarely studied in glioma. In this study, 1493 glioma samples (data from our cohort, TCGA, and CGGA) expressing METTL7B were used to explore its prognostic value and mechanism in immune microenvironment. Results showed that high expression of METTL7B is associated with poor prognosis and abundant immunosuppressive cells. Further, functional enrichment showed that METTL7B is involved in negative regulation of immunity and carcinogenic signaling pathways. Moreover, a METTL7B-related prognostic signature constructed based on multi-omics, showed good prediction of overall survival (OS) time of glioma patients. In conclusion, METTL7B is a potential prognostic biomarker. In addition, the prognostic prediction model constructed in this study can be used in clinical set-ups for development of novel effective therapeutic strategies for glioma patients and improve OS.